Role of Health Literacy on Menstrual Hygiene Practice among the Girl Students - Khanal, Shanti Prasad (Journal of Health Promotion, 2019)
The main aim of this study was to find out the role of health literacy on menstruation hygiene practice of campus girls. The population of this study were girls studying health and physical education in Surkhet Campus and HA/Staff Nurse in SEDA Campus. Surkhet was selected by proportional stratified sampling. This study followed descriptive and cross-sectional design. The study used two tools Short Test of Functional Health Literacy in Adults (S-TOFHLA) and Self Administrated Questionnaire for collecting data. It was found that health literacy among girls of study area is not satisfactory. The findings indicate that 53.93 percent respondents have adequate health literacy. Adequate health literacy level of girls of HA/Staff nurse, aged 16-18 years and 19-21 years and Chhetri and Janajati had adequate health literary. The findings support that higher proportions of the adequate health literate respondents have good menstruation hygiene practice than inadequate health literate respondents. Finally, the results indicated that health literacy among the girls is inadequate, that calls more concern to the matter of health literacy in educational programs.